Comportamientos y condiciones inseguras en personal operativo del área de incineración, con exposición al riesgo biológico en una empresa de disposición final de residuos. 2015- 2018 (2018)
The Ministry of Environment and Sustainable Development (Min Ambiente - Colombia) as public sector in charge of environmental conservation is dedicated to research, collection and management of information on the waste generated by the different sectors and is responsible for making proposals to classify and zone this waste based on to different characteristics, hence the importance of knowing how the handling should be carried out of waste, its characteristics and final disposal.